Straight Forward and Versatile Differentiation of the l-glycero and d-glycero-d-manno Heptose Scaffold - Suster, Christoph; Baxendale, Ian R.; Mihovilovic, Marko D.; Stanetty, Christian (Frontiers in Chemistry, 2020)
Bacterial lipopolysaccharides (LPS) are important bio-medical structures, playing a major role in the interaction with human immune systems. Their core regions, containing multiple units of L-glycero-D-manno heptoses (L,D-heptose), are highly conserved structurally (with O3 and O7 glycosidic bonds), making them an epitope of high interest for the potential development of new antibiotics and vaccines. Research in this field has always been restricted by the limited availability of the parent L,D-heptose as well as its biochemical epimeric precursor D-glycero-D-manno heptose (D,D-heptose). This problem of availability has recently been solved by us, through a rapid and efficient practical synthesis of L,D-manno-heptose peracetate demonstrated at scale. Herein we report an optimized, technically simple and versatile synthetic strategy for the differentiation of both the L-glycero and D-glycero-D-manno heptose scaffold. Our approach is based on an orthoester methodology for the differentiation of all three positions of the sugar core using a O6,O7-tetraisopropyl disiloxyl (TIPDS) protecting group for the exocyclic positions. Furthermore, the regioselective opening towards 7-OH acceptors (6O-FTIPDS ethers) differentiates the exocyclic diol which has been demonstrated with a broader set of substrates and for both manno-heptoses for the first time.